Ottoman Empire, Borno, and Rabih: A Complicated Relation Between the 1840s and 1900s - Duymus, Kerem (Center for Research and Documentation in Trans-Saharan Studies, 2025)
The history of Borno during the 19th century still lacks a considerable picture regarding the relations between Borno and the Ottoman Empire. This article presents, for the first time, a substantial compilation of Ottoman archival sources from Turkey and Libya, thereby illuminating the previously neglected subject of political and diplomatic relations between the Ottoman Empire and Borno from the 1840s to 1893. Numerous new findings indicate that there was not only a very dens diplomatic relation between two states, but they even created a new political system incorporating Borno into the Ottoman rule, ensuring the further autonomy of the Al-Kanemi dynasty. Furthermore, additional discoveries reveal the intricate diplomatic dynamics between the Ottoman Empire and Rabih from 1893 to 1900, thereby offering a fresh perspective on the historical context of both Rabih and Borno.
Keywords: Borno; Ottoman Empire; Sahara; Rabih; Al-Kanemi; Africa; West Africa